SGK1 drives hippocampal demyelination and diabetes-associated cognitive dysfunction in mice - Ziying Jiang; Bin Liu; Tangsheng Lu; Xiaoxing Liu; Renjun Lv; Kai Yuan; Mengna Zhu; Xinning Wang; Shangbin Li; Song Xu; Xinyu Wang; Yifei Wang; et al. (Nature Communications)
Abstract Diabetes-associated cognitive dysfunction (DACD) is increasingly recognized as a critical complication of diabetes. The complex pathology of DACD remains unknown. Here, we performed single-nucleus RNA sequencing (snRNA-seq) to demonstrate unique cellular and molecular patterns of the hippocampus from a mouse model of diabetes. More in-depth analysis of oligodendrocytes (OLs) distinguished five subclusters, indicating different functional states of OLs and transcriptional changes in each subcluster. Based on the results of snRNA-seq and experiments in vivo, we observed demyelination and disharmony of oligodendroglial lineage cell composition in male diabetic mice. Serum/glucocorticoid regulated kinase 1 (SGK1) expression was significantly increased in the hippocampus OLs of male diabetic mice, and SGK1 knockdown in hippocampus reversed demyelination and DACD via N-myc downstream-regulated gene 1 (NDRG1)-mediated pathway. The findings illustrated a transcriptional landscape of hippocampal OLs and substantiated impaired myelination in DACD. Our results provided direct evidence that inhibition of SGK1 or the promotion of myelination might be a potential therapeutic strategy for DACD.